BMP9 Promotes an Epithelial Phenotype and a Hepatocyte-like Gene Expression Profile in Adult Hepatic Progenitor Cells - Annalisa Addante; Carlos González-Corralejo; Cesáreo Roncero; Nerea Lazcanoiturburu; Juan García-Sáez; Blanca Herrera; Aránzazu Sánchez (Cells, 2022)
Bone morphogenetic protein 9 (BMP9), a member of the TGF-β superfamily, has emerged as a new player in chronic liver diseases (CLDs). Its levels increase in the fibrotic liver where it promotes fibrogenesis. It also regulates hepatic progenitor cells (oval cells in rodents), a cell population that contributes to repopulate the liver and recover functionality upon severe damage, but it can also be pro-fibrogenic, depending upon the hepatic microenvironment. Here we analyze the effect of chronic exposure to BMP9 in oval cells. We show that cells chronically treated with BMP9 (B9T-OC) display a more epithelial and hepatocyte-like phenotype while acquiring proliferative and survival advantages. Since our previous studies had revealed a functional crosstalk between BMP9 and the HGF/c-Met signaling pathways in oval cells, we analyzed a possible role for HGF/c-Met in BMP9-induced long-term effects. Data evidence that active c-Met signaling is necessary to obtain maximum effects in terms of BMP9-triggered hepatocytic differentiation potential, further supporting functionally relevant cooperation between these pathways. In conclusion, our work reveals a novel action of BMP9 in liver cells and helps elucidate the mechanisms that serve to increase oval cell regenerative potential, which could be therapeutically modulated in CLD.